Advances in Molecular Genetics of Reproductive Isolation in Rice - Shunmei LI; Zihan ZHENG; Ruiying LIU; Hongze GUO; Lin ZHENG; Yongyao XIE (Guangdong nongye kexue)
Reproductive isolation (RI) refers to the phenomena that different populations cannot mate to produce offsprings under natural conditions, or the produced offsprings cannot survive or are sterile. It plays an important role in speciation and maintaining species stability, and is the core scientific issue of evolutionary biology. There are extensive interspecific and intersubspecific RI in rice, which is an ideal model to study RI. Additionally, interspecific and intersubspecific hybrids display strong heterosis in rice due to the distant genetic relationship, but they suffer from serious RI which restricts the effective utilization of distant heterosis. The scientists have made great progress in cloning the causal genes and expounding the molecular genetic basis of RI in rice, which not only deepen our theoretical understanding of the rice evolutionary biology, but also greatly promote the development of distant hybrid rice breeding. To date, more than 60 RI loci have been identified, and the related genes of 15 RI loci have been cloned in rice. The scientists have proposed five molecular genetic models of RI in rice, including one-locus killer-protector model, one-locus killer-target model, one-locus sporophytic interaction model, two-locus duplicate gametic lethal model and two-locus sporophytic interaction model. According to these findings, several strategies and methods such as developing wide compatibility lines, breeding intersubspecific introgression rice and establishing artificial hybrid compatible lines by genome editing have been proposed to overcome RI in rice. Based on the rice model, this review summarizes the advances of RI in rice, including RI types, molecular genetic basis and overcoming strategies, and provides a forward-looking perspective on the development trend and challenges in the field of rice RI, with an aim to provide ideas and references for further study of molecular genetic mechanism of plant RI and distant crop hybrid breeding.